Estereótipos da velhice e cultura organizacional: um estudo de suas relações em uma instituição de longa permanência para idosos - Blanco, Ana Luiza (Universidade Federal de São Carlos, 2020)
Population aging is a worldwide phenomenon that it’s becoming increasingly more representative in Brazil. Among the different scenarios to be rethought for this new reality, this study prioritizes a discussion about the Organizational Culture in a Long Term Care Institution for Elderly (LCIF) and it’s reflections on the Aging Stereotypes. The potentialization of certain stereotypes can compromise the quality of life of people who internalize such conceptions. Considering this problem, the purpose was to analyze how aging stereotypes, as perceived by the users of and those who work at a LCIF, are reflected by cultural traits of the organization. The study was conducted in a private LCIF and participated in this study employees and residents of the institution. It was used a qualitative approach, using the strategy of a single case study for a better deepening of the institutional analysis. Data collection was applied through the following instruments: Field Diary, Observations Records and a Case Study Protocol, composed by a Semi-Structured Interview. All interviews were transcribed. For the analysis of the material, the rules of categorizations, evidences, chains of evidences and conclusions were followed. The results demonstrate that the organization culture of the institution may be contributing to the perpetuation of negative stereotypes of aging related to dependence, cognitive decline, loss of autonomy, sadness, loneliness and second childhood. Initiatives that promote changes in the organizational culture are important strategies to minimize the identified stereotypes, insuring new ways of care and the social ressignification of aging.
Stereotypes of aging and organizational culture: a study of their relations in a long term care institution for elderly
Keywords: Cultura organizacional; Estereótipos do envelhecimento; Instituição de longa permanência para idosos; Organizational culture; Age stereotypes; Long term care institution for elderly; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO